Response of growing rabbits (Oryctolagus cuniculus) fed diets containing raw tallow (Detarium microcarpum) seed meal - Jiya Zhiri E.; Abdumojeed Ijaiya T.; John Alabi O.; John Makinde O.; Salamatu Saidu (Journal of Agricultural Sciences (Belgrade), 2018)
A 12-week study was conducted to determine the effect of graded levels of raw tallow seed meal (RTSM) on growth performance, haematological and biochemical parameters and organoleptic qualities of growing rabbits. Five experimental diets were compounded to contain 0, 25, 50, 75 and 100% RTSM replacing the palm kernel cake weight for the weight designated as T1, T2, T3, T4 and T5, respectively. Forty-five (45) weaned rabbits between 5 and 6 weeks with an average body weight ranging from 500 to 600 g of mixed breeds and sexes (females and males) were randomly allocated to the five (5) dietary treatments in the randomized complete block design with nine (9) rabbits per treatment replicated three (3) times with three (3) rabbits each. Data were collected on feed intake, weight gain, feed conversion ratio, nutrient digestibility, some haematological and biochemical parameters and organoleptic qualities of the rabbits. The feed intake, weight gain and feed conversion ratio were significantly (P<.005) affected by the dietary treatments. The rabbits fed diets T1, T2 and T3 recorded similar feed intake (62, 66.95, and 66.50 g), total weight gain (1328.73, 1320.44, and 1323.49 g) and feed conversion ratio (3.92, 4.26, and 4.22) which were significantly better than those observed for the rabbits fed diets T4 and T5. The nutrient digestibilities of the rabbits fed the experimental diets were also significantly (P<0.05) affected. The rabbits fed diet T2 had better fiber digestibility (47.05%) compared to other treatment groups. Ether extract digestibility was observed to be better in the group of rabbits fed diets T1, T2 and T3, respectively. Some of the other nutrients in the group of rabbits fed diets T3, T4 and T5 were similarly digested. The haematological parameters were observed to be depressed as the level of RTSM increased in the diets. Packed cell volume, red blood cells and white blood cells were observed to reduce from 37.69 to 21.22%, 4.14 to 2.18 g/dl and 4.98 to 3.02 g/dl. The biochemical parameters indicated a similar trend as that of the haematological parameters. Total protein, glucose and urea reduced from 6.15 to 4.63 g/dl, 5.15 to 3.80 g/dl and 7.76 to 4.00 mmol/l. The result of the organoleptic qualities indicated a non-significant (P>0.05) difference except for the juiciness which was significantly (P<0.05) high in the rabbits fed diets T1 (5.90), T3 (5.65), and T4 (5.90), respectively. In conclusion, up to 50% of RTSM can be included in the diets of rabbits without adverse effects on productive performance, nutrient utilization, blood parameters and organoleptic qualities.